Improvement of WBAN performances by a hybrid model: design and evaluation of a novel inter-MAC layer exploited in medical applications. Issue 1 (2019) - Zaouiat, C.E. Ait; Latif, A.
The main idea of this paper is essentially motivated by the need to set up a smooth transition towards the IEEE 802.15.6 standard, which is doomed to take over versus IEEE 802.15.4 standard in the future, which is of a great interest. In this paper, since IEEE 802.15.4 is more efficient for sensors with minimum data rate requirement, for sensors enquiring high data rates, the use of IEEE 802.15.6 is more advantageous, whence our contribution aims to improve the wireless body area networks (WBANs) performance by combining both IEEE 802.15.4 and IEEE 802.15.6 advantages in one hybrid WBAN design. A new design so called the inter-MAC layer is suggested, which is located between the dependent-technology MAC layers and upper protocols layers, playing the role of a smart communication bridge. Ultimately, a comparative evaluation study is conducted between the two combined models (i.e., IEEE 802.15.4 and IEEE 802.15.6) with the new hybrid design, which led to a considerable improvement in terms of the lifetime and the reliability.